Speculation, Now : Essays and Artwork - Kuoni, Carin; Krishnamurthy, Prem, 1977-; Rao, Vyjayanthi Venuturupalli (Book collections on Project MUSE., 2014)
Interdisciplinary in design and concept, Speculation, Now illuminates unexpected convergences between images, concepts, and language. Artwork is interspersed among essays that approach speculation and progressive change from surprising perspectives. A radical cartographer asks whether ""the speculative"" can be represented on a map. An ethnographer investigates religious possession in Islam to contemplate states between the divine and the seemingly human. A financial technologist queries understandings of speculation in financial markets. A multimedia artist and activist considers the relation.